Effect of paprika xanthophyll supplementation on oxygen uptake in athletes: a randomized, double-blind, placebo-controlled study - Ichihara, T.; Nishino, A.; Takaha, T.; Kuriki, T.; Nihei, H.; Yasui, H.; Maoka, T.; Kawamoto, K. (The Journal of Physical Fitness and Sports Medicine, 2018)
Xanthophylls have been attracting attention as phytochemicals with antioxidant activity and various beneficial effects demonstrated by randomized clinical trials. Ripe red paprika has high xanthophyll content and is a valuable source of dietary xanthophylls. Our previous study revealed that paprika xanthophylls were detected in the plasma of healthy volunteers after oral administration and preferentially accumulated in erythrocytes, suggesting a potential beneficial effect on erythrocytes. The present study was performed to investigate the effect of paprika xanthophyll supplementation on respiratory parameters in athletes performing treadmill exercise. In a randomized, double-blind, placebo-controlled, parallel group study, 14 athletes were assigned to daily intake of a drink containing 9.0 mg of paprika xanthophylls or a placebo drink. Before and after the 4-week intervention period, blood samples were collected to measure plasma carotenoid levels. The athletes also performed treadmill exercise (12 km/hr for 20 min) before and after the 4-week intervention period, and respiratory parameters were analyzed. After 4 weeks, the paprika xanthophyll group had significantly higher levels of total plasma xanthophylls and total plasma carotenoids (p = 0.014 and 0.043, respectively) than the placebo group. VO2, VCO2, and VE were significantly lower in the paprika xanthophyll group than the placebo group. These results suggest that paprika xanthophyll supplementation allowed athletes to perform exercise at a set intensity with lower oxygen uptake. Subjective fatigue after exercise was also significantly less severe in the paprika xanthophyll group.